2021
DOI: 10.1002/cbf.3669
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual blood CD146+ mesenchymal stem cells reduced fibrosis rate in the rat model of premature ovarian failure

Abstract: Here, the regenerative potential of menstrual blood-derived mesenchymal stem cells (MenSCs) was examined on restoration of premature ovarian failure (POF) ovaries in rats' POF model. Freshly isolated CD146 + MenSCs using magnetic-activated cell storing method were immediately injected into ovaries of POF rats. Four and eight weeks after cell administration, both ovarian tissues were sampled for histological examination and the expression of fibrosis-related genes. Serum samples were also prepared for hormonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…Finally, the fertility of music-treated mice was assessed after eight weeks. According to the results of previous studies, we also showed that the number of offspring in POF rats exposed to music was more related to the non-treated POF group [12,56,9].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Finally, the fertility of music-treated mice was assessed after eight weeks. According to the results of previous studies, we also showed that the number of offspring in POF rats exposed to music was more related to the non-treated POF group [12,56,9].…”
Section: Discussionsupporting
confidence: 71%
“…Different clinical symptoms such as amenorrhea, hypoestrogenism (estrogen reduction), and hyper-gonadotropism (increased levels of gonadotropins) can be manifested in POF women [6]. Until now, various pre-clinical strategies have been developed for the treatments of POF including hormone replacement therapy (HRT), gonadotropin-releasing hormone (GnRH) application, and modalities that are associated with the application of whole-cell, or cell-based products [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the fertility of music-treated mice was assessed after eight weeks. According to the results of previous studies, we also showed that the number of offspring in POF rats exposed to music was more related to the non-treated POF group [ 9 , 12 , 56 ].…”
Section: Discussionsupporting
confidence: 64%
“…We first established a POI mouse model by injecting CTX (90 mg/kg dose), Various dosages and procedures have been used to induce POI in animals [ 28 , 29 ]. CTX is the most commonly used chemotherapeutic drug.…”
Section: Discussionmentioning
confidence: 99%